Research techniques for scholars and students in religion and theology - Tucker, Dennis C. (Information Today, 2000)
"A good foundation in research skills is an essential part of a good education and an important asset in continued lifetime learning. In the fields of religion and theology there are six major components essential to the development of information retrieval and utilization. Dennis Tucker's latest book covers such important aspects as overall library layout, library staff functions, library catalogs, reference collections, periodical literature, electronic resources, research documentation, and paper development."--